On the chain equivalence of projective chain complexes - Khmelnitskii, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We obtain a necessary and sufficient condition for $n$-dimensional chain complexes composed of finitely generated projectivemodules to be stabilized by free modules to the chain equivalence.